Public attitudes in Australia to the reintegration of ex-offenders:: testing a belief in redeemability (BiR) scale - O'Sullivan, Kevin (European journal on criminal policy and research, 2017)
We report the results of a large scale Australian survey of public attitudes to offender reintegration. A representative sample of 1215 respondents gave their views about the possibility that offenders could make a good life for themselves after having committed crime. Views expressed were significantly positive with around four out of five respondents indicating they believed reintegration was possible and should be attempted. On the basis of the responses an overall score was calculated for each respondent. Analysis of the data suggested that three factors contributed to the overall score. We named these: Human capital, Possibility of change and Agency and the rationale for these is discussed. Some demographic factors (age, gender, presence of children in the household and highest level of schooling) were significantly related to scores in one of the components. Respondents also reported whether they, or someone close to them, had been a victim of crime or had been arrested, and whether they had worked in the field of law enforcement or the field of human services. Inclusion in these categories was found to be significantly related to certain components of the overall score. These findings are discussed in the light of related surveys in other jurisdictions and we invite other researchers to use the scale and suggest improvements.